Doris Duke Clinical Research Fellowship: Report of the Second Annual Meeting. (1st November 2003) - Allen, Alisha; Parikh, Gunjan; McPhaul, Michael J.
Abstract : The second annual national meeting of the Doris Duke Charitable Foundation Clinical Research Fellowship for Medical Students program was held June 24 to 26, 2003, at Cold Spring Harbor Laboratory near Long Island Sound. This 3-day meeting offered an opportunity for 63 of the 2002 Doris Duke clinical research fellows, program directors, administrators, and invited physician-scientists to present and share their research with one another in an informal, inspiring setting at an institution with a history that mirrors the development of modern American medical research. Following a keynote lecture by Dr. Kenneth Davis, dean of the Mount Sinai School of Medicine, six physician-scientists representing different areas of clinical research presented their work. Oral and poster presentations by the Doris Duke fellows of their research were interspersed throughout the meeting and comprised its central focus. The fellows' research spanned a broad spectrum of clinical research from studies translating basic research findings to those addressing clinical questions to epidemiologic and health outcomes studies. The meeting culminated in a forum entitled "'Where Do We Go from Here?' Residency Selection and Further Research Training in Pursuit of a Career as a Clinician-Scientist, " which was moderated by this year's clinical research fellow national program leader, Dr. Allyn L. Mark. The meeting celebrated the accomplishments of these talented medical students during their fellowship year and, it is hoped, instilled in them awareness that their continued efforts are important to the future progress of medicine.